The Impact of Sustainability Reporting on Profitability in Iraq Stock Exchange: Role of the Transparency as Moderating Variable - Al-Dulaimi, Anmar Adnan Khudhair; Abdulrasool Jaber Al Mamoori, Mohammed; Jawad Al-Khafajy, Eman; Abed, Ahmed Neaah (ExcelingTech, 2020)
Abstract This study has examined moderating impact of transparency on relation between the sustainability reporting disclosure on profitability. The study’s statistical population consisted of listed companies in Iraq Stock Exchange for period 2014 to 2017, which in this study content of 25 corporation sample was analyzed to assess the level of corporations’ disclosing sustainability reporting through annual reports on the activities of the board. Secondary data from annual report of Iraq corporations were used actualize the research objectives In this study. Panel data regression techniques namely fixed effects estimation and random effects estimation in addition to pooled Ordinary Least Square regression was carried out on the secondary data collected from corporations reports. For this purpose, 167 Disclosure indices were analyzed based on Triple Bottom Line (TBL) in three economic, social and environmental dimensions using a zero-one procedure and rating of each corporation’s disclosing corporate social responsibility was extracted to determine their level of disclosure. To investigate the association between variables of this research, the level of corporations’ disclosing sustainability reporting independent variable and performance metrics based on accounting data (ROA) as dependent variable are considered. Based on the research results, there is a significant relationship between the level of disclosing corporate social responsibility and financial performance criteria of corporations based on both accounting data. Moreover, results of this study can increase individual investors’ confidence in investing in companies with stronger corporate governance. This finding provides new evidence to the literature as well as for the policy makers to consider on transparency adoption.